Serum Homocysteine Level Predictive Capability for Severity of Restenosis Post Percutaneous Coronary Intervention - Guo, Jiqiang; Gao, Ying; Ahmed, Mohammad; Dong, Pengfei; Gao, Yuping; Gong, Zhihua; Liu, Jinwen; Mao, Yajie; Yue, Zhijie; Zheng, Qingli; Li, Jiansheng; Rong, Jianrong; et al. (Frontiers in Pharmacology, 2022)
Background: In stent restenosis (ISR) is one of the major complications after stent implantation. Thus, there is a growing interest in identifying a biomarker for the onset of ISR. High levels of serum homocysteine (Hcy) have been associated with the progression of cardiovascular disease. Therefore, the study was carried out to quantify the correlation between serum Hcy and ISR severity. Compared with coronary angiography (CAG), Hcy levels provided a significantly better clinical detection of ISR severity after PCI. Methods: A total of 155 patients were recruited from Shanxi Bethune hospital, from 6 months to 2 years post PCI. Serum Hcy levels and postoperative angiography results were used to differentiate the patients into two experimental groups: ISR (>50% diametrical stenosis), and non-ISR. The non-ISR included two subgroups: intimal hyperplasia (10–50% diametrical stenosis), and recovery (<10% diametrical stenosis). In addition, a group of 80 healthy individuals was used as a negative control. The correlation between homocysteine level and ISR severity t was analyzed for all groups. In addition, the correlation between serum Hcy level and the severity of ISR in the experimental group was analyzed by the Pearson correlation test. Results: The serum Hcy level in the experimental group and control group was determined to be (20.21 ± 11.42) μmol/L and (15.11 ± 10.25) μmol/L respectively. The level of serum Hcy in the experimental group was significantly higher than in the control group (t-value of 2.385; p-value of 0.019). The serum Hcy level in the restenosis and the intimal hyperplasia group was (25.72 ± 13.71) μmol/L and (17.35 ± 7.70) μmol/L respectively. The serum Hcy level in the restenosis group was significantly higher than in the intimal hyperplasia group (t-value of 2.215; p-value of 0.033). The level of serum Hcy in the group without a plaque in the stent was (16.30 ± 6.08) μmol/L, whereas in the control group was (15.11 ± 10.25) μmol/L. The no plaque group had a slightly higher serum Hcy level than the control group (t-value of 0.634; p-value of 0.528). All included patients were divided into four quartiles based on the serum Hcy concentration: quartile 1 (8.90–13.20 μmol/L), quartile 2 (13.30–16.45 μmol/L), quartile 3 (16.60–24.25 μmol/L) and quartile 4 (24.30-65.30 μ mol/L). The incidence of ISR was 5, 6.25, 7.5 and 15%, in the 1,2,3 and four quartiles respectively. The serum Hcy level in the experimental group was (20.21 ± 11.42) μmol/L, the severity of in-stent restenosis was (0.25 ± 0.31), (R-value was 0.234; p-value was 0.037), indicating a correlation between serum Hcy and the severity of restenosis (p < 0.05). Taking coronary angiography as the gold standard, a ROC curve analysis was performed on the serum Hcy levels for the experimental group. The area under the curve (AUC) was 0.718 (95% CI 0.585-0.854, p < 0.001), indicating that the serum Hcy concentration could predict ISR. On the ROC curve, the best critical value of serum Hcy concentration for predicting ISR was 20.05 μmol/L, with a sensitivity of 45% and specificity of 88.1%. Conclusion: A positive correlation was observed between homocysteine and the severity of restenosis after PCI, The level of Hcy could serve as a predictive biomarker for the severity of ISR.